2019
DOI: 10.37358/rc.19.10.7584
|View full text |Cite
|
Sign up to set email alerts
|

Resistance and Virulence Features in Carbapenem-resistant Acinetobacter baumannii Community Acquired and Nosocomial Isolates in Romania

Abstract: We aimed to identify the virulence and antimicrobial resistance features in Carbapenem Resistant Acinetobacter baumannii (CRAB) strains isolated from hospital settings and compare them with those isolated in the same period of time from community acquired (CA) infections in Bucharest, south of Romania. A total number of 93 A. baumannii strains were isolated in majority from hospitalized patients and from CA infections. The resistance and virulence mechanisms of the strains were characterized by phenotypic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…For A. baumannii, two acquired CHLDs encoding genes were revealed in the analyzed strains: bla OXA-23 and bla OXA-24 . The same results were found by Gheorghe et al (2019) in their study [32]. Most of the strains of P. aeruginosa were positive for bla IMP (Supplementary Figure S4) and bla VIM (Supplementary Figure S5).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…For A. baumannii, two acquired CHLDs encoding genes were revealed in the analyzed strains: bla OXA-23 and bla OXA-24 . The same results were found by Gheorghe et al (2019) in their study [32]. Most of the strains of P. aeruginosa were positive for bla IMP (Supplementary Figure S4) and bla VIM (Supplementary Figure S5).…”
Section: Discussionsupporting
confidence: 82%
“…Another pathogen that is also an important biofilm producer is A. baumannii [57], an opportunistic pathogen with major implications in HAIs, responsible for outbreaks and severe infections especially in patients with different immunodeficiencies. Although poor in the production of soluble VF (in our study, almost all of the strains produced only one VF-ompA) (see Supplementary Figure S15), it proved to be an important nosocomial pathogen due to the formation of biofilms (especially on medical devices) and due to its MDR, XDR, or PDR phenotypes [30,32,58,59]. Compared with the soluble VF reported for other Gram-negative bacteria, a small number of these factors have been identified for A. baumannii, in comparison with K. pneumoniae and P. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
“…The strains were screened for CP ( bla VIM , bla IMP , bla NDM , bla KPC for Pa ), and bla OXA-51/69-like , bla OXA-23-like , bla OXA-24-like , bla OXA-58-like , bla OXA-143 , bla OXA-235, bla NDM genes in the case of Ab strains) and ESBL encoding genes ( bla CTX-M , bla TEM , bla SHV , bla PER , bla VEB , bla GES for strains belonging to both species) using previously described primers and PCR protocols [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Romania, in contrast to clinical studies [27,28,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61], there is little information available on the epidemiology of AMR reservoirs in the environment, especially in polluted water and rivers. We have previously shown that MDR, CP and ESBL-producing K. pneumoniae isolated from clinics, hospital wastewater and urban WWTPs from different regions of the country exhibit multiple antibiotic and antiseptic resistance, as well as virulence genes, with the ST101 clone being the most frequently encountered in all sampling sites [62].…”
Section: Table 3 Args In Clinical and Wastewater Pa Strains Isolated ...mentioning
confidence: 99%
“…Simplex and multiplex PCR were used to screen the presence of carbapenem-and cephalosporin-encoding genes (bla VIM , bla IMP , bla NDM , bla KPC , bla GES , bla SHV , bla TEM , bla CTX-M , bla PER , bla VEB , bla OXA-23 , bla OXA-24 , bla OXA-58 , bla OXA-235 , and bla OXA-51 ), as well as for VM detection (ompA, epsA, csuE, bap, and bfmS) using a DNA template extracted with an alkaline extraction method, specific primers, and amplification programs (Table 1) and checked with gel electrophoresis [28]. Positive strains for the investigated genes were used as the positive controls.…”
Section: Characterization Of Resistance and Virulence Profiles Of Ab ...mentioning
confidence: 99%